نظرية الاعتراف بين أكسل هونث ونانسي فريزر - Hanifi, Djamila (Université de M'sila, 2020)
The Theory of Recognition between Axel Honneth and Nancy Fraser Abstract Although Nancy Fraser has distinguished the principle of recognition from the principle of redistribution of economic goods and benefits, she believes that it is not possible to build a coherent concept of justice by focusing on one principle alone, but that both concepts should be given importance. Axel Honneth sees that the source of the problem lies in the theoretical tools that allow the redistribution, which in his view requires the elaboration of a theory of recognition at first hand. So he views the two principles as two sides of the same coin. Based on the above, this paper will deal with the following questions: what are the reasons of the philosophical debate between Honneth and Fraser on the principle of recognition? What is recognition? Is it a matter of justice or self-achievement? To answer these questions we will first address recognition as a self-realization, according to Honneth, then secondly recognition as justice, according to Frazer.
Keywords: Recognition, Redistribution, Self-achievment, Justice, Offense, Values, Parity